2020
DOI: 10.1152/ajpendo.00121.2019
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling protein 1 and the capacity for nonshivering thermogenesis are components of the glucose homeostatic system

Abstract: Uncoupling protein 1 (Ucp1) provides nonshivering thermogenesis (NST) fueled by the dissipation of energy from macronutrients in brown and brite adipocytes. The availability of thermogenic fuels is facilitated by the uptake of extracellular glucose. This conjunction renders thermogenic adipocytes in brown and white adipose tissue (WAT) a potential target against obesity and glucose intolerance. We employed wild-type (WT) and Ucp1-ablated mice to elucidate this relationship. In three experiments of similar setu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 70 publications
3
31
0
Order By: Relevance
“…The presence of UCP1 is essential for this effect at least in lean mice housed at sub‐thermoneutral temperatures. It has been recently reported that UCP1 knockout mice exhibit lower glucose uptake in thermogenic tissues with compensatory increases in WAT and skeletal muscle in an oral glucose tolerance test 44 . Our results imply that these compensatory mechanisms, if further induced by mirabegron in UCP1 knockout mice, are unable to significantly affect postprandial glucose uptake in these tissues to result in substantial increases in glucose tolerance.…”
Section: Discussionmentioning
confidence: 50%
“…The presence of UCP1 is essential for this effect at least in lean mice housed at sub‐thermoneutral temperatures. It has been recently reported that UCP1 knockout mice exhibit lower glucose uptake in thermogenic tissues with compensatory increases in WAT and skeletal muscle in an oral glucose tolerance test 44 . Our results imply that these compensatory mechanisms, if further induced by mirabegron in UCP1 knockout mice, are unable to significantly affect postprandial glucose uptake in these tissues to result in substantial increases in glucose tolerance.…”
Section: Discussionmentioning
confidence: 50%
“…It is known that BAT of cold-exposed Ucp1 -/displays mitochondrial dysfunction, ER stress and inflammation (37,38,76), processes that have been implicated in the development of insulin resistance (37) and reduced cellular glucose uptake (77)(78)(79)(80). In line with an alteration in insulin sensitivity, it has been found that when fed a high fat diet Ucp1 -/mice display impaired glucose clearance (81). Thus, the lower glucose uptake, as well as the associated reduction of lipogenic enzymes, in BAT of acute and chronically activated Ucp1 -/mice (Figures 3 and 4) may be explained by insulin resistance.…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that Ucp1 À/À mice have impaired adrenergic activation of metabolic rate following four weeks of high fat feeding and that their relative increase in body weight is greater than wild-type animals at thermoneutrality whether fed chow or high fat diet [85]. However, independent investigators have reported that body weight regulation in Ucp1 À/À mice is identical to wild-type animals fed a high fat diet at thermoneutrality [86,91,[94][95][96]. Moreover, severe loss of UCP1 protein in BAT because of other genetic manipulations also does not result in obesity at thermoneutrality [97][98][99][100][101][102].…”
Section: Ebf2mentioning
confidence: 99%